Measuring determinants of exchange rate in Sudan: Standard Statistical Study - Osman, Hassan Ali; Alfadl, Asim Mohammed; Adam, Sofian Abuelbacher (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to measure the important determinants of exchange rate in Sudan within the period (1999 – 2019), the study problem lies in the main question: why is Sudanese economy for long time suffering from instability of exchange rate? Descriptive Analytical method was used in theoretical side of the study and tools of econometrics in analysis was used in practical side. The study’s data for that period was collected from the Central Bureau of Statistics and Central Bank of the Sudan. The study assumed some hypotheses, the most important one is that there is inverse relationship having a negative impact statistically between inflation and exchange rate in Sudan. The study has concluded to the existence of a negative relationship between inflation and exchange rate, and a positive relationship between foreign direct investment and exchange rate in Sudan, also study concluded to impact of Inflation, Export, Gross Domestic Production and Foreign Direct Investment on exchange rate by 98%. The study has recommended to necessity of a deflationary monetary policy to control inflation and to achieve the exchange rate stability.
Keywords: inflation; exports; gross domestic product; foreign direct investment